2018
DOI: 10.2478/congeo-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Structural setting of the Koum sedimentary basin (north Cameroon) derived from EGM2008 gravity field interpretation

Abstract: This study is a contribution to the planning of hydrocarbon exploration program of the Koum sedimentary basin in North Cameroon. 3D modeling of WGM2012 gravity data derived from EGM2008 geopotential model in the Koum basin was used together with existing geological and spectral analysis information to give structural picture of the basin. The 3D model of the Koum basin confirms that the basin is developed as a half graben bounded by sub-vertical faults. The thickness of the Cenozoic sediments is about 1.5 km i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…These changes were found to occur on the upward continued maps up to depth of 35 km. Therefore, lineaments can be viewed as a succession of linear features (HD maxima) that can be related to the trend of the existing faults in the study area as suggested by Koumetio et al ( 2012) and Shandini et al (2018). The gravity and magnetic lineaments detected here are traced out in Figs.…”
Section: Detection and Mapping Of Lineamentssupporting
confidence: 53%
“…These changes were found to occur on the upward continued maps up to depth of 35 km. Therefore, lineaments can be viewed as a succession of linear features (HD maxima) that can be related to the trend of the existing faults in the study area as suggested by Koumetio et al ( 2012) and Shandini et al (2018). The gravity and magnetic lineaments detected here are traced out in Figs.…”
Section: Detection and Mapping Of Lineamentssupporting
confidence: 53%
“…In this work, the localized maxima for each anomaly depth were superimposed (Figure 6) for the lineament plot (Figure 7). Therefore, the lineaments can be considered as a succession of characteristic lineaments that may be related to the trend of existing faults in the study area [7] [31] [42]. Application of this method to Bouguer anomaly maps shows that superimposed…”
Section: Multiscale Analysis Of Bouguer Anomalies Horizontal Gradient...mentioning
confidence: 99%
“…From a geological point of view, the crust in Cameroon is characterized by two main geological structures, the Pan-African-Mobile Belt in the north and the Congo Craton in the south, with several main structural features such as the Sanaga Fault, the Cameroon volcanic line, and the Adamawa Plateau [29][30][31][32][33][34][35][36][37][38]. These features have been partially modeled using various geophysical methods such as gravity, magnetic, 4 Geofluids and seismic data [29][30][31][32][33][34][35][36][37][38]. From the review of [29][30][31][32][33][34][35][36][37][38], it comes out that the geological structures and features of Cameroon have been shaped by tectonic activity over millions of years, and that those main features are the following:…”
Section: Global and Regional Trends In Geothermal Energymentioning
confidence: 99%